The Association of Smoking and Alcohol Abuse on Anxiety and Depression in Patients With Recurrent Acute or Chronic Pancreatitis Undergoing Total Pancreatectomy and Islet Autotransplantation: A Report From the Prospective Observational Study of TPIAT Cohort. Issue 6 (July 2021) - Lara, Luis F.; Wastvedt, Solvejg; Hodges, James S.; Witkowski, Piotr; Wijkstrom, Martin; Walsh, R. Matthew; Singh, Vikesh K.; Schwarzenberg, Sarah J.; Pruett, Timothy L.; Posselt, Andrew; Naziruddin, Bashoo; Nathan, Jaimie D.; et al.
Abstract : Objectives: Smoking and alcohol use are risk factors for acute and chronic pancreatitis, and their role on anxiety, depression, and opioid use in patients who undergo total pancreatectomy and islet autotransplantation (TPIAT) is unknown. Methods: We included adults enrolled in the Prospective Observational Study of TPIAT (POST). Measured variables included smoking (never, former, current) and alcohol abuse or dependency history (yes vs no). Using univariable and multivariable analyses, we investigated the association of smoking and alcohol dependency history with anxiety and depression, opioid use, and postsurgical outcomes. Results: Of 195 adults studied, 25 were current smokers and 77 former smokers, whereas 18 had a history of alcohol dependency (of whom 10 were current smokers). A diagnosis of anxiety was associated with current smoking ( P = 0.005), and depression was associated with history of alcohol abuse/dependency ( P = 0.0001). However, active symptoms of anxiety and depression at the time of TPIAT were not associated with smoking or alcohol status. Opioid use in the past 14 days was associated with being a former smoker ( P = 0.005). Conclusions: Active smoking and alcohol abuse history were associated with a diagnosis of anxiety and depression, respectively; however, at the time of TPIAT, symptom scores suggested that they were being addressed.